Pengaruh Kualitas Layanan Terhadap Kepuasan Pelanggan Pengguna Jasa JNE Cabang Santi Kota Bima - Risman; Sri Ernawati2; Juwani (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
This research aims to find out whether there is a significant influence of Marketing Mix on this research aims to determine the influence of service quality on customer satisfaction of JNE service users at Santi Bima City Branch. The type of research used is associative research with a quantitative approach. The research sample of 50 respondents were selected with purposive sampling techniques, namely JNE service users who have used the service at least twice. Data was collected through a questionnaire with the Likert scale and analyzed using validity tests, reliability, simple linear regression, correlation coefficients, determination coefficients, and t tests with the help of the SPSS program version 22. Research results show that service quality does not have a significant effect on customer satisfaction. This is proven by a count value of -1,676 < 1,677 with a significance value of 0,100 (> 0,05). The correlation coefficient value of 0.235 which is in the low category, and the determination coefficient of 0.055 which means that the service quality variable is only able to explain 5.5% of customer satisfaction variation, while 94.5% is influenced by other factors that are not researched. The conclusion from this study is that the quality of the service does not have a significant impact on the satisfaction of JNE service users at the Santi Branch of Bima City. Therefore, it is recommended to JNE to improve aspects of service, such as punctuality of delivery, communication, and courier professionalism to be able to increase customer satisfaction.